Heavy metal pollution diagnosis and ecological risk assessment of the surrounding soils of coal waste pile at Naluo Coal Mine, Liupanshui, Guizhou. Issue 4 (3rd July 2016) - Ge, Hao; Feng, Yun; Li, Yang; Yang, WenLi; Gong, Ning
Abstract : In accordance with the National Soil Environmental Quality Standards of China, Grade I and Grade II (GB15618-1995), this study adopted single pollution index (SPI) and Nemeiow synthetical pollution index (NSPI) methods to analyse and assess the ecological risk of the seven heavy metals, namely Cd, Hg, As, Cu, Pb, Cr and Zn, contained in the surrounding soils of one coal waste pile at Naluo Coal Mine, Liupanshui, Guizhou, China. The results revealed that (1) Cd had higher SPI than any other heavy metal and the maximum Cd SPI, indicative of serious pollution, was found in the soil sample collected from the 150 m distant from the centre along possible coal gangue alluvial flow; (2) synthetical pollution assessment of heavy metals per Grade I found that soil sample collected from sites 150 m from the centre along possible coal gangue alluvial flow had the maximum NSPI, which suggests that the soil is seriously polluted, and that there is a link between heavy metal pollution level in the surrounding soils of the coal waste pile and the sampling direction; (3) synthetical pollution assessment of heavy metals per Grade II revealed that sampling distance had a bearing on the pollution level in the surrounding soils of the coal waste pile, and the soil samples collected from 100 or 150 m distant in all the sampling paths had minor pollution.